Upaya Peningkatan Kesehatan Mental Pada Remaja di RW O1 Galur-Jakarta Pusat - Pasaribu, Jesika; Lisum, Kristina; Aini, Jeni Nur (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2025)
Mental health for adolescents is important to recognize and improve adolescents' psychological well-being and resilience. Adolescents with good mental health have adaptive abilities to manage feelings and deal with the challenges of daily life. The results of the initial study in student-managed families found that the majority of families expressed adolescents' vulnerability to mental health problems due to the impact of technological advances. Providing health education is expected to increase adolescents' self-recognition and increase knowledge to improve mental health. The community service method begins with the problem collection stage in the fostered area and continues with providing health education on the characteristics of adolescents/Gen Z and the importance of maintaining mental health at a young age. The results of filling out the questionnaire showed that the majority of adolescents, 73.68%, were in the moderate Psycho-logical Well-Being category and 52.63% were in the moderate Psychological Distress category. It is expected that adolescents can increase self-awareness and improve mental health in overcoming problems in everyday life.Keywords: adolescents; gen Z; mental health Abstrak: Kesehatan mental untuk remaja penting untuk mengenali dan meningkatkan kesejahteraan psikologis dan ketahanan remaja. Remaja dengan kesehatan mental yang baik memiliki kemampuan adaptif untuk mengelola perasaan dan menghadapi tantangan kehidupan sehari-hari. Hasil studi awal pada keluarga kelolaan mahasiswa, ditemukan mayoritas keluarga mengutarakan kerentanan remaja pada masalah kesehatan mental akibat dampak kemajuan teknologi. Pemberian edukasi kesehatan diharapkan dapat meningkatkan pengenalan diri remaja dan meningkatkan pengetahuan untuk meningkatkan kesehatan mental. Metode pengabdian masyarakat dimulai dengan tahap pengumpulan masalah pada wilayah binaan dan dilanjutkan dengan pemberian edukasi kesehatan mengenai karakteristik remaja/Gen Z dan pentingnya menjaga kesehatan mental pada usia muda. Hasil pengisian kuesioner diketahui bahwa mayoritas remaja, sebesar 73.68% berada pada kategori Psychological Well-Being tingkat sedang dan 52.63% berada pada tingkat Psychological Distress kategori sedang. Diharapkan remaja dapat meningkatkan kesadaran diri dan meningkatkan kesehatan mental dalam mengatasi masalah dalam kehidupan sehari-hari.Kata kunci:  remaja; gen Z; kesehatan mental